Hubungan Pengetahuan Pencemaran Lingkungan Dengan Environmental Responsibility - Cindy Putri Hapsari; Arwin Surbakti; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This research aims were to determine the significance, closeness, and direction of relation, also the amount of contribution between environmental pollution knowledge with environmental responsibility. The method of this research was correlation. Subjects of this research were 101 students grade VIII Junior High School 7th Bandar Lampung. Data of knowledge were obtained by multiple choice tests while data of environmental responsibility were obtained from using questionnaire. Data were analyzed by using simple linear regression analysis method. The results showed that there was significant correlation between knowledge with environmental responsibility, with significant value that was 0,000. Level of correlation was weak that was indicated the value of correlation coefficient that was 0,224. There was positive correlation between knowledge with environmental responsibility that showed by the regression equation Y=47.898+0,347x, so the relation between knowledge with environmental responsibility was unidirectional. And, there was very low contribution between knowledge to environmental responsibility which indicated that 5% of determinant coefficient.Penelitian ini bertujuan untuk mengetahui signifikansi, keeratan, dan arah hubungan, serta besarnya kontribusi antara pengetahuan pencemaran lingkungan dengan environmental responsibility. Metode penelitian ini adalah metode korelasional. Subyek penelitian adalah siswa kelas VIII SMP Negeri 7 Bandar Lampung sebanyak 101 siswa. Data pengetahuan diambil menggunakan tes pilihan jamak sedangkan data environmental responsibility diambil menggunakan kuesioner. Analisis data menggunakan metode analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara pengetahuan dengan environmental responsibility, dengan nilai signifikasi 0,000. Tingkat keeratan hubungan adalah lemah, dengan nilai koefisien korelasi 0,224. Terdapat hubungan yang positif antara pengetahuan dengan environmental responsibility yang ditunjukkan melalui persamaan regresi Y=47.898+0,347X sehingga arah hubungan antara pengetahuan dengan environmental responsibility adalah searah. Serta terdapat kontribusi yang sangat rendah antara pengetahuan terhadap environmental responsibility dengan koefisien determinansi sebesar 5%.Kata kunci: lingkungan, pencemaran, pengetahuan, responsibility